The Effect of Process Selection and Layout on Productivity: A Case Study in Micro, Small and Medium Enterprises - Clarisa, Cindy; Niami, Sinta; Hariyati, Hariyati; Lusiana, Lusiana (UPI YPTK Journal of Business and Economics, 2025)
The study aims to discover the effect of process selection and layout on Micro, Small and Medium Enterprises (MSMEs) Productivity. The unit of analysis is Micro, Small and Medium Enterprises (MSMEs) in Padang City. The study utilized primary data which is obtained through the questionnaire. Sampling technique by using quota sampling. 100 questionnaires from MSMEs were returned as a final sample. Data were analyzed using multiple regression analysis performed by SPSS software. The result shows that process selection positively and significantly affects MSMEs productivity. Layout has a positive and significant effect on organizational performance. The combined impact of process selection and layout results in increased throughput, reduced production costs, and higher overall productivity. MSMEs that invest in aligning their process and layout strategies are better equipped to overcome operational challenges, adapt to changing market demands, and maintain competitiveness